2022
DOI: 10.22146/ijg.68184
|View full text |Cite
|
Sign up to set email alerts
|

Green Open Space Priority Modelling Using GIS Analysis in West Jakarta

Abstract: Green open space is one of the most important land uses, especially in densely populated urban areas. Public Green Open Land in each area regulated in Law No. 1 of 2007 is at least 20%. Based on data from the Department of Creative Works, Land and Spatial Planning as well as the Environment Agency of DKI Jakarta, West Jakarta's Green open space asset area is 277.45 Ha of the total area of West Jakarta, which is 12543 Ha. There is a need for a study to determine the potential land for green open space in West J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…This decline had a significant impact on the quality of life and well-being of the city residents, as these spaces played a critical role in urban sustainability, including the health and happiness of its inhabitants. According to previous studies, community interviews in West Jakarta revealed a substantial demand for cities with environmental parks [33]. This demand highlights the need to facilitate urban activities and enhance the local urban environment to provide better experiences and amenities to communities.…”
Section: Green Open Spaces (Gos) In Jakartamentioning
confidence: 94%
“…This decline had a significant impact on the quality of life and well-being of the city residents, as these spaces played a critical role in urban sustainability, including the health and happiness of its inhabitants. According to previous studies, community interviews in West Jakarta revealed a substantial demand for cities with environmental parks [33]. This demand highlights the need to facilitate urban activities and enhance the local urban environment to provide better experiences and amenities to communities.…”
Section: Green Open Spaces (Gos) In Jakartamentioning
confidence: 94%
“…Changes in land use in areas that are not planned will create problems in spatial planning. Therefore, it is necessary to formulate policies for the management and development of urban green spatial planning to improve the quality of the urban living environment (Aryaguna et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Green open space (RTH) is one of the zones included in the protected area in the RDTR spatial pattern plan for the urban area of Malinau Regency which consists of public green open space and private green open space (Aryaguna et al, 2022). Public green open space (RTH) with a proportion of 20% generally consists of city parks, public cemeteries, and green belts along roads, rivers, and beaches.…”
Section: Introductionmentioning
confidence: 99%